Trajectory Tracking of AR.Drone Quadrotor Using Fuzzy Logic Controller - Agung Prayitno; Veronica Indrawati; Gabriel Utomo (Universitas Ahmad Dahlan, 2014)
In this paper, Fuzzy Logic Controller (FLC) is implemented in the AR.Drone quadrotor in order to make it follow a given trajectory reference. The distance between the position and angle of the AR.Drone to the reference point is used as the input of FLC. As for the output, pitch value and yaw rate will be the controlling signal for the AR.Drone. The navigation data of the AR.Drone are forward speed (vx), sideward speed (vy), and yaw. These navigation data are going to be used to estimate positions and orientation of the AR.Drone. To compensate the y-position drift, the value of vyis also use as a criterion to determine the roll compensation. The FLC algorithm is implemented to AR.Drone 2.0 Elite Edition using LabVIEW software. Also, the algorithm has been tested in various trajectories such as straight line, a straight line with a perpendicular turn, a rectangular trajectory, and a curved trajectory. The results have shown that AR.Drone can follow a given trajectory with various initial position and orientation quite well.